2016
DOI: 10.1248/cpb.c15-00689
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Selenium-Binding Proteins in the Brain Using Its Reactive Metabolite

Abstract: The intracellular metabolism of selenium in the brain currently remains unknown, although the antioxidant activity of this element is widely acknowledged to be important in maintaining brain functions. In this study, a comprehensive method for identifying the selenium-binding proteins using PenSSeSPen as a model of the selenium metabolite, selenotrisulfide (RSSeSR, STS), was applied to a complex cell lysate generated from the rat brain. Most of the selenium from L-penicillamine selenotrisulfide (PenSSeSPen) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Yoshida et al [29] reported a comprehensive method for identifying the selenium-binding proteins using PenSSeSPen as a model of the selenium metabolite, selenotrisulfide (RSSeSR, STS), which was applied to a complex cell lysate generated from the rat brain. The authors stated that a thiol-containing protein at m/z 15155 in the brain cell lysate was identified as the cystatin-12 precursor (CST12) from a rat protein database search and a tryptic fragmentation experiment.…”
Section: Brain Antioxidant Homeostasy In Relation To Selenium and Gshpxmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshida et al [29] reported a comprehensive method for identifying the selenium-binding proteins using PenSSeSPen as a model of the selenium metabolite, selenotrisulfide (RSSeSR, STS), which was applied to a complex cell lysate generated from the rat brain. The authors stated that a thiol-containing protein at m/z 15155 in the brain cell lysate was identified as the cystatin-12 precursor (CST12) from a rat protein database search and a tryptic fragmentation experiment.…”
Section: Brain Antioxidant Homeostasy In Relation To Selenium and Gshpxmentioning
confidence: 99%
“…CST12 belongs to the cysteine proteinase inhibitors of the cystatin superfamily that are of interest in mechanisms regulating the protein turnover and polypeptide production in the central nervous system and other tissues. Consequently, CST12 is suggested to be one of the cytosolic proteins responsible for the selenium metabolism in the brain [29].…”
Section: Brain Antioxidant Homeostasy In Relation To Selenium and Gshpxmentioning
confidence: 99%
“…According to previously reported procedures [14,15], X-ray photoelectron spectroscopy (XPS) was performed using an AXIS-ULTRA instrument fitted with a delay-line detector and a monochromated Al Kα line (0.8339 nm, 1.486 keV) operating at 10 kV and 13 mA (Shimadzu Corp., Kyoto, Japan).…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…The main selenoproteins in blood are selenoproteins P which contribute approximately 50% of the total plasmatic selenium and glutathione peroxidase which count 10-30% of selenium in plasma [ 4 ]. In the brain, selenium concentration is reported to be far less variable than those in the peripheral tissues and organs [ 5 ]. This fact implied the importance of selenium for maintaining the integrity of brain functions and the distinctive selenium metabolism and the regulatory mechanism in the brain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, selenium concentration is reported to be far less variable than those in the peripheral tissues and organs [ 5 ]. This fact implied the importance of selenium for maintaining the integrity of brain functions and the distinctive selenium metabolism and the regulatory mechanism in the brain [ 5 ]. Otherwise, studying the relationship between selenium and progression of patients suffering from brain disorder such as traumatic brain injury (TBI) may be useful.…”
Section: Introductionmentioning
confidence: 99%